(untitled) (Journal of Applied Membrane Science & Technology, 2025)
Pyrolyzed coconut copra biochar (PCB) is a primary byproduct produced during the pyrolysis process of coconut copra biomass. This study focused on the effect of increasing pyrolysis temperature on the characteristics and hexavalent chromium (Cr(VI)) removal potential of the PCB as adsorbent and membrane precursor. Copra, a readily available agricultural waste in Malaysia, was utilized as the biochar precursor to produce PCB at 300-500 °C, 5 °C/min heating rate and 1 hour residence time. Then, PCB was incorporated into a polyvinylidene fluoride (PVDF) membrane using the dry/wet phase inversion technique, with varied biochar loadings (0 to 1 wt.%). The produced PCB were characterized using CHNS elemental analysis, Fourier transform Infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), Brunaue-Emmett-Teller (BET) surface analysis and pH drift analysis to assess morphology, functional groups, surface area, porosity and pH point of zero charge, respectively. Adsorption isotherm study shows the best fit with Langmuir and Freundlich model. Adsorption kinetics study shows pseudo-second order model fit better than the pseudo-first-order model. Then, preliminary incorporation tests of optimized PCB in PVDF membrane analyzed using water uptake and porosity analysis, water contact angle and performance analysis via cross flow system to assess water flux and Cr(VI) removal. It was found at 450 °C pyrolysis temperature produced copra biochar with relatively high carbon content of 72 %, the highest pore volume of 6.168 10-3 cm3/g with adsorption capacity of 10.41 mg/g and Cr(VI) removal of 27.98 %. As PCB loading in the PVDF membranes increased from 0 to 0.4 wt.%, it was found that the membrane porosity increased from 7 % to 62 % resulted in the enhancement of the water flux achieving maximum 2.04 Lm-2h-1 at 0.5 g/L loading and Cr(VI) removal achieving 33.33 %. This has shown good potential of copra biochar as adsorbent and incorporation to develop adsorptive membrane for heavy metal removal.